2015
DOI: 10.5152/ejp.2015.39974
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Hemangioma (Pneumocytoma) of the Lung: An Analysis of 8 Cases

Abstract: Objective: We aimed to evaluate clinical manifestations, radiological findings, treatment, and outcomes of pulmonary sclerosing hemangioma (SH). Methods:We retrospectively reviewed eight cases of pulmonary sclerosing hemangioma diagnosed at our institution from January 2006 to April 2014. Their demografic findings, symptoms, radiological appearences, diagnostic methods, treatments and surveys were recorded.Results: There were four female and four male patients. The age at the time of diagnosis ranged from 23 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The maximum diameters of SP in our patients varied from 1 to 2.5 cm. According to other studies, lesions range from 0.3 to 7 cm in greatest dimension [2,4,6]. Some authors have assumed that clinical symptoms can be evident due to enlargement and consequent pressure on adjacent lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum diameters of SP in our patients varied from 1 to 2.5 cm. According to other studies, lesions range from 0.3 to 7 cm in greatest dimension [2,4,6]. Some authors have assumed that clinical symptoms can be evident due to enlargement and consequent pressure on adjacent lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Although its name implicated a vascular neoplasm, further studies have reported the possible pulmonary epithelium (pneumocyte type II) origin of this tumor. This conclusion has been strongly supported by immunohistochemical findings, and that is why alternative terms, such as pneumocytoma, sclerosing pneumocytoma, or papillary pneumocytoma, have been suggested [2]. In the newest World Health Organization (WHO) classification of lung and pleural tumors from 2015, it has been classified under the more convenient name pneumocytoma [3].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum diameter of the pneumocytoma in our patient was >7 cm. According to other studies, lesions range from 0.3 to 7 cm in greatest dimension [2,12,5,6]. Some authors have assumed that clinical symptoms can be evident due to enlargement and consequent pressure on adjacent lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Although its name implicated a vascular neoplasm, further studies have reported the possible pulmonary epithelium (pneumocyte type II) origin of this tumor. This conclusion has been strongly supported by immunohistochemical findings, and that is why alternative terms, such as pneumocytoma, sclerosing pneumocytoma, or papillary pneumocytoma, have been suggested [2], [3]. In the newest World Health Organization (WHO) classification of lung and pleural tumors from 2015, it has been classified under the more convenient name pneumocytoma [4[, [3].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemically, round stromal cells were TTF-1 and EMA (+), and pancytokeratin (-). The surface epithelium was TTF-1, EMA, and pancytokeratin (+), and CEA, S100, smooth muscle actin, chromogranin-a, and CD34 negative (2,7,13). Vascular tumors, carcinoid tumor, and pulmonary hamartoma were considered in the discriminative diagnosis.…”
Section: Discussionmentioning
confidence: 99%